Relationship Between Empowerment Level and Profile of Farm Women Attending Vocational Training Programme (Indian Journal of Extension Education, 2020)
Empowering women and reducing gender inequalities are one of the major components of development objectives. The present study was conducted in Bhimtal district of Nainital to study the, profile characteristic of farm women and its relationship with empowerment level as a result of vocational training programme. The findings of the study showed that, empowerment level was found to be influenced by their profile characteristics. Variables like age, land holing and annual income etc. showed non-significant association with empowerment level in both beneficiaries and non beneficiaries. The result also shows that empowerment had significant association with selected independent variables such as scientific orientation, and risk orientation. Therefore, the concerned organizations and personnel may manipulate those characteristics for improving the psychological, social and economic empowerment of farmwomen.